Influence of aggression, proximity, dominance and grooming on bond strengths of pairs of female plains zebras in captivity - Ang, Serena Yue Ling (2009)
This present study aims to investigate whether the four parameters: aggression, proximity, dominance and grooming influence the bond strengths of pairs of female plains zebras. A herd of female plains zebras (N = 5) in captivity in the Singapore Zoological Gardens was studied. Markers of aggression, proximity, dominance and grooming were scored during the 52 hr 20 min of observations and input into sociomatrices. These sociomatrices were analysed using Matman (DeVries et al., 1993). Results showed that there is a linear dominance hierarchy present in the study group which further proved that social bonds are strong. Findings from this study also state that dominant individuals give more aggression and; pairs that spend more time in proximity give more grooming but not aggression to each other. These findings were statistically proven. Results were compared to and discussed with other studies that examined bond strengths in harem-living equids or group-living mammals as well. This study has also incorporated the variable of proximity which has not been widely studied in equids and will thus contribute to studies on them.